Polyacrylonitrile Hard Carbon as Anode of High Rate Capability for Lithium Ion Batteries - Rao, Xianfa; Lou, Yitao; Chen, Jun; Lu, Haichao; Cheng, Bin; Wang, Weiting; Fang, Hui; Li, Hualin; Zhong, Shengwen (Frontiers in Energy Research, 2020)
In order to develop new type of carbon anode material with high performance, a novel organic carbon material polyacrylonitrile (PAN) hard carbon was prepared by calcination of polypropylene cyanide at 1050 °C. The obtained PAN hard carbon is used as the negative electrode material of lithium ion battery, showing an initial capacity of 343.5 mAh g-1 which is equal to that of graphite electrode (348.6 mAh g-1), and a higher initial coulomb efficiency of 87.9% than that of graphite electrode (84.4%). Moreover, the PAN hard carbon electrode shows superior cycle stability and rate performance at different current rates. The charge capacities are 320.1, 219.0, 212.9 and 123.5 mAh g-1 at current rates of 0.2 C, 1 C, 2 C and 3 C, with coulombic efficiencies of 98.1%, 100.6%, 88.1% and 110.0%, respectively, which are higher than those of graphite electrode (83.8%, 97.6%, 98.8% and 94.1%). In addition, the charging capacity of PAN hard carbon electrode can still remain at 284.3 mAh g-1 (0.2 C after 200 cycles), 226.4 mAh g-1 (1 C after 300 cycles), 149.5 mAh g-1 (2 C after 400 cycles) and 120.0 mAh g-1 (3 C after 100 cycles), with capacity retention rates of 78.2%, 111.9%, 79.7% and 88.6%, respectively. The capacity and capacity retention rate after cycling are significantly higher than those of graphite electrode, indicating that the PAN hard carbon electrode shows superior rate performance, which would provide a new idea for the development of novel negative electrode material with high performance.